Exploring the Human Wildlife interface in Social Forestry Division Bareilly, Uttar Pradesh - Tomar, Virat Singh; Rout, Sandeep; Rawat, Vijaya (Indian Forester, 2019)
Study was conducted on the Exploring the Human Wildlife interface, offences and community aspects in Social Forestry Division Bareilly, Uttar Pradesh in 2013-2015. The study method consisted of data collection from primary and secondary resources and the wild animals pug mark, killing the animals and attack on humans in different villages of Social Forestry Division Bareilly. The sighting was recorded from agriculture fields, village cottages, along Behgul River, water tank, graveyard and near the rivulet. Rural areas were infested with the conflicts of nilgai, black buck, rhesus macaque, wild pig, jackal and snake conflicts. A few cases of tiger/leopard conflict and problems due to bird species were also reported. The data received from the Social Forestry Division, Bareilly showed that 1183 problematic rhesus macaques were captured from different locations of Bareilly namely municipal corporation Bareilly, villages like Simra Ajuba Begam and Rajau Paraspur villages. These monkeys were released by the Forest department to natural habitat. Road accident by wild animals and snake bite cases was also reported during the survey.